Tutor’s Role in WhatsApp Learning Groups: A Quali-Quantitative Methodological Approach - Annese, Susanna; Amenduni, Francesca; Candido, Vito; McLay, Katherine Francis; Ligorio, Maria Beatrice (Frontiers in Psychology, 2022)
In recent years, digital tools such as WhatsApp have been increasingly deployed to support group interaction and collaboration in higher education contexts. To understand contemporary, digitally-mediated collaborative dynamics – including the role played by tutors and the situated nature of group development – robust and innovative methodologies are needed. In this paper, we illustrate how integrating qualitative methods with quantitative tools used in qualitative ways makes it possible to trace how tutors adapt their style to support group development, which in turn triggers student development in a circular and responsive process. To make visible this contemporary phenomenon, we combine thematic content analysis – a qualitative tool – with a quantitative method: Social Network Analysis. Drawing on data generated by two WhatsApp learning groups (six students and four academic tutors) in research exploring the collaborative construction of boundary objects in a master’s level “E-learning Psychology” course, we suggest that our methodological approach has the potential to support interrogation of complex and dynamic digitally-mediated group interactions. Our results show the situational nature of an effective tutorship style through its complex adaptation to learners’ maturity, digital tools and learning goals.